2021
DOI: 10.1002/anie.202100299
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Carbene Transfer Reactions of Aryl/Aryl Diazoalkanes—Experiment and Theory**

Abstract: Controlling the reactivity of carbene intermediates is ak ey parameter in the development of selective carbene transfer reactions and is usually achieved by metal complexes via singlet metal-carbene intermediates.I nt his combined experimental and computational studies,w es how that the reactivity of free diaryl carbenes can be controlled by the electronic properties of the substituents without the need of external additives.T he introduction of electron-donating and -withdrawing groups results in as ignifican… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
130
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 55 publications
0
130
0
3
Order By: Relevance
“…这类重氮化合物在可见光照射下进行光解产生 游离态卡宾, 这也是目前可见光促进重氮转化反应中应 用最多的底物类型. 近期, Koenigs 课题组 [7] 发现, 修饰 后的二芳基重氮化合物也可在蓝色 LED 照射下产生卡 宾物种, 随后发生后续的环丙烯化等反应. 近几年来, 由于可见光诱导重氮化合物的转化反应具有操作简单、 无需使用金属催化剂等优势, 以及符合绿色化学等理 念, 吸引了越来越多科研工作者的关注.…”
unclassified
“…这类重氮化合物在可见光照射下进行光解产生 游离态卡宾, 这也是目前可见光促进重氮转化反应中应 用最多的底物类型. 近期, Koenigs 课题组 [7] 发现, 修饰 后的二芳基重氮化合物也可在蓝色 LED 照射下产生卡 宾物种, 随后发生后续的环丙烯化等反应. 近几年来, 由于可见光诱导重氮化合物的转化反应具有操作简单、 无需使用金属催化剂等优势, 以及符合绿色化学等理 念, 吸引了越来越多科研工作者的关注.…”
unclassified
“…Recently, Koenigs and co‐workers found that the aryl/aryl diazoalkanes could serve as efficient singlet carbene precursors under blue LED irradiation and the formed carbene species have been applied to cyclopropenation, cascade, and C−H functionalization reactions [16] . To further expand the reaction types of diaryl carbene intermediates, we next investigated the reactivity of aryl/aryl diazoalkanes under our standard reaction conditions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Die Reaktion von Diazoalkanen unter photochemischen, metallfreien Bedingungen geht auf einen frühen Bericht von Meerwein [4] zurück. Neuste Entwicklungen nutzen nun die photochemischen Eigenschaften von Donor‐Akzeptor‐Diazoalkanen 2 , welche Licht im sichtbaren Spektrum absorbieren, um auf diese Weise freie, reaktive Carbene zu erzeugen und in effizienten, nachhaltigen Carbentransferreaktionen nutzbar zu machen, [2, 5–7] wie beispielsweise in der Darstellung von Cyclopropenen ( 5 , Schema 1b) [5c] . Unter photokatalytischen Bedingungen können durch Anregung eines geeigneten Photokatalysators jedoch grundlegend andere Reaktionswege, z.…”
Section: Methodsunclassified